METAFORA DALAM LIRIK LAGU BAHASA JEPANG KARYA KENSHI YONEZU - Rodiyanti, Puput; Hermandra, Hermandra; Aibonotika, Arza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the forms and meanings of metaphors contained in the Japanese song lyrics in Kenshi Yonezu's album